Characterization and whole genome sequencing of Saccharomyces cerevisiae strains lacking several amino acid transporters: Tools for studying amino acid transport - Unnati Sonawala; Aymeric Busidan; David Haak; Guillaume Pilot (PLoS ONE, 2025)
Saccharomyces cerevisiae mutants have been used since the early 1980s as a tool for characterizing genes from other organisms by functional complementation. This approach has been extremely successful in cloning and studying transporters; for instance, plant amino acid, sugar, urea, ammonium, peptide, sodium, and potassium transporters were characterized using yeast mutants lacking these functions. Over the years, new strains lacking even more endogenous transporters have been developed, enabling the characterization of transport properties of heterologous proteins in a more precise way. Furthermore, these strains provide the added possibility of characterizing a transporter belonging to a family of proteins in isolation, and thus can be used to study the relative contribution of redundant transporters to the whole function. We focused on amino acid transport, starting with the yeast strain 22 ∆ 8AA, which was developed to clone plant amino acid transporters in the early 2000s. We recently deleted two additional amino acid permeases, Gnp1 and Agp1, creating 22 ∆ 10α. In the present work, five additional permeases (Bap3, Tat1, Tat2, Agp3, Bap2) were deleted from 22 ∆ 10α genome, in a combination of up to three at a time. Unexpectedly, the amino acid transport properties of the new strains were not very different from the parent, suggesting that these amino acid permeases play a minor role in amino acid uptake, at least in our conditions. Furthermore, the inability to utilize certain amino acids as sole nitrogen source did not correlate with reduced uptake activity, questioning the well-accepted relationship between lack of growth and loss of transport properties. Finally, in order to verify the mutations and the integrity of 22 ∆ 10α genome, we performed whole-genome sequencing of 22 ∆ 10α using long-read PacBio sequencing technology. We successfully assembled 22 ∆ 10α’s genome de novo, identified all expected mutations and precisely characterized the nature of the deletions of the ten amino acid transporters. The sequencing data and genome will serve as a valuable resource to researchers interested in using these strains as a tool for amino acid transport study.